Towards Understanding the Role of Trust in Electronic Business - Seppo Sirkemaa (International Association of Research and Science, 2022)
Electronic Business is based on trust between the seller and the buyer. Trust is not an issue if seller and buyer know each other, and they have an existing business relationship. However, when there are no earlier experiences, when the customer is not familiar with the vendor or the products and services this can be challenging. If there is no knowledge whether the vendor is trustworthy, the buyer is trying to find different kinds of cues and experiences to make sure the decisions are right. Here we look at how these cues could be made available, by adding value to both vendor and buyer. Ultimately, better information increases trust, and helps in developing successful business.